The effects of the scheme for BCG vaccination of schoolchildren in England and Wales and the consequences of discontinuing the scheme at various dates. Issue 1 (March 1989) - Sutherland, I; Springett, V H
Abstract : The aims of this paper were to estimate the numbers of tuberculosis notifications in young white adults which will be prevented in the next 25 years by the schools BCG vaccination scheme, and to assess the numbers of additional notifications if the scheme were to be discontinued. Assuming that in the white ethnic group in England and Wales the decline in tuberculosis notification rates (8-10% per year for ages less than 45 years) and efficacy of BCG vaccination (75-80%) are maintained, it is estimated that the scheme for BCG vaccination of schoolchildren with its present coverage will prevent 217 notifications in those aged 15-29 years in 1993, 119 in 1998, and 69 in 2003. The epidemiological consequences of stopping the BCG in schools scheme, whenever this occurs, would be a substantial slowing of the rate of decline of tuberculosis notifications, confined almost entirely to the 15-29 years age group, for a period of about 15 years, after which the steeper decline would resume. If the scheme stopped at the end of 1991 the annual number of additional notifications would slowly increase to a maximum of just over 80 about 15 years later, and then decrease. For stopping at the end of 1996 the maximum annual number of additional notifications would be about 50.